Safety and performance evaluation of a next‐generation antimicrobial dressing in patients with chronic venous leg ulcers. Issue 4 (21st June 2015) - Harding, Keith G; Szczepkowski, Marek; Mikosiński, Jacek; Twardowska‐Saucha, Krystyna; Blair, Stephen; Ivins, Nicola M; Saucha, Wojciech; Cains, Jane; Peters, Kim; Parsons, David; Bowler, Philip
Abstract: The objective of this study was to investigate the safety and performance of AQUACEL™ Ag+ dressing, a wound dressing containing a combination of anti‐biofilm and antimicrobial agents, in the management of chronic wounds. Patients ( n = 42) with venous leg ulcers exhibiting signs of clinical infection were treated for 4 weeks with AQUACEL™ Ag+ dressing, followed by management with AQUACEL™ wound dressings for 4 weeks. Wound progression, wound size, ulcer pain and clinical evolution of the wound were assessed for up to 8 weeks. Adverse events were recorded throughout the study. AQUACEL™ Ag+ dressing had an acceptable safety profile, with only one patient discontinuing from the study, because of a non‐treatment‐related adverse event. After 8 weeks, substantial wound improvements were observed: 5 patients (11·9%) had healed ulcers and 32 patients (76·2%) showed improvement in ulcer condition. The mean ulcer size had reduced by 54·5%. Patients reported less pain as the study progressed. Notable improvements were observed in patients with ulcers that were considered to require treatment with systemic antibiotics or topical antimicrobials at baseline ( n = 10), with a mean 70·2% reduction in wound area. These data indicate that AQUACEL™ Ag+ dressing has an acceptable safety profile in the management of venous leg ulcers that may be impeded by biofilm.